Risk Factors for Carpal Tunnel Syndrome in Informal Sector Workers: Literature Review - Hubaybah Hubaybah; Muhammad Iqbal; Budi Aswin; Ismi Nurwaqiah Ibnu; La Ode Reskiaddin (International Journal of Medicine and Health, 2022)
CTS is one of the diseases that occurs in many workers so it is often referred to as work-related Carpal Tunnel Syndrome. The high number of informal workers allows for high accidents in the workplace. The purpose of this study is to discuss the risk factors for the incidence of CTS in informal sector workers. This research is a descriptive research with the literature review method. The literature search strategy uses a prism flow chart, and inclusion and exclusion criteria. The databases used include: PubMed, Taylor and francis, and Google Scholar. From the 20 articles, 19 of them used the cross-sectional type of research, and 1 article used the case-control type of research. The types of informal work obtained from the 20 articles are: motorcycle taxi drivers, farmers, batik and bead craftsmen, blacksmiths, stone breakers, meatball sellers, coconut peelers, woodcarvers, tailors, angkot drivers, small-scale convection, hairstylists, and butchers. Overall, the journal articles obtained discuss related to the risk factors for the incidence of CTS in informal sector workers. Repetitive movements, length of service, length of work, hand posture (awkward), age, gender, and body mass index were found to influence the incidence of CTS in informal sector workers. Meanwhile, grasping work and a history of diabetes mellitus were not found to be related to the incidence of CTS in informal sector workers.